Contribution of Female Entrepreneurs in Promoting Local Food to Support Tourism in Bali - Sucita Yanthy, Putu; Darma Putra, N.; Bendesa, I Komang Gde (E-Journal of Tourism; Volume 3 Number 2 (September 2016), 2016)
This study analyzed the contributions of Balinese female entrepreneurs in the culinary industry in promoting local food to support tourism in Bali. Research was undertaken in the area of Bali province and data were obtained from observations, interviews and study of literature supported by the theory of invented tradition. Eight Balinese warrior of culinaries were interviewed supported by food bloggers, literature reviews and documentation. Data were analyzed based on descriptive qualitative. The results show that Balinese female entrepreneurs have: (1) popularized Balinese food, (2) preserved the existence of Balinese food, (3) strengthened the Balinese culinary identity, and (4) supported tourism in Bali.
Keywords: balinese food; women' s contributions